Adaptation and validation of the scenario test in greek - Tayma El Riz, Thekla (q, 2021)
Background: This study explores the psychometric qualities of The Scenario Test GR, an adapted version of The Scenario Test UK developed by Hilary et al. in 2018. The Scenario Test GR assess daily – life function communication abilities for people with aphasia (PWA) in an interactive setting, with a supportive communication partner. Aims: To determine and examine the reliability (internal consistency, test- retest and interrater reliability) and validity (convergent, discriminant and known – groups validity) of the Greek version of The Scenario Test. Methods & Procedures: The Scenario Test GR and seven other measures of language, communication, cognition and psychosocial domain were administered to participants. The sample included 23 participants with aphasia and 17 participants without aphasia. All participants were stroke survivors (6+ months post – stroke) and recruitment was performed from Cyprus. Outcomes & Results: The Scenario Test GR showed high levels of reliability and validity. Internal consistency (Cronbach’s α = 0.94), interrater reliability (total score) (ICC = 0.98) and test – retest reliability (ICC = 0.99). Good convergent validity was indicated with 4 measures (ρ = -0.45 – 0.82) and good discriminant validity (ρ = 0.33). The test demonstrated good known – groups validity (U = 74.0, p < 0.001), with significantly higher scores of participants without aphasia compared to those with aphasia. Conclusions: The psychometric qualities of The Scenario Test GR are highly corresponding with those of those of The Scenario Test UK. The findings support the reliability and validity of the test, as a measure of functional communication for PWA. Further testing is needed to measure sensitivity to change.
Keywords: The Scenario Test GR; Functional communication; People with aphasia (PWA); Instrument adaptation; The Scenario Test GR; Λειτουργική επικοινωνία; Άτομα με αφασία (PWA); Προσαρμογή οργάνων